Gambaran USG Leiomioma Uteri Pada Dewasa : LITERATURE REVIEW - Anthonius Christopher Wisnu; Sony Sutrisno; Adrian Setiawan; Monica Cherlady Anastasia (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Uterine myoma is one of the most common tumors found in premenopause. Symptoms that can arise vary, ranging from asymptomatic to symptoms that interfere with daily activities. The most common symptoms arise, namely pain and vaginal bleeding. Women who have, myoma diagnosed certainly emits risk factors. Risk factors that can aggravate, among them are heredity, obesity, hormonal contraception, nullipara, hypertension, primipara age <20 years, deficiency of vitamins D Risk Factors Risk of land can be able to be able That, as for effective modalities is used for supporting examinations of uterine uterine and MRI uterine myomas. Ultrasound can be done as an initial screening, while MRI is better used for a more appropriate location when compared to ultrasound.